Implementation Of Productive Waqf Operational Management at Nurul Huda Mosque in Metro City - Adi Putra, Bangun (Nuban Jagadhita Centre, 2023)
Purpose: This research aims to find out and analyze the implementation of productive waqf operational management at the Nurul Huda Ganjang Agung Mosque, Metro City. Methodology: This research uses a type of field research with descriptive qualitative research. The data in this study were collected using interview and documentation techniques. Data analysis techniques in this research are data collection, reduction, presentation, verification, and conclusions. Findings: The results of the analysis of productive waqf operational management at the Nurul Huda Mosque in Metro City can be concluded that the operational management of productive waqf at the Nurul Huda Mosque has not been carried out properly. Productive waqf operational management has not carried out the process function properly, namely, the process of distributing waqf is still limited to the operational use of the Nurul Huda mosque. The implementation of the capacity function has not been good in its calculations and the capacity of cultivators who are only worked on by 8 people, consisting of 7 cultivators for 9 fields of rice fields and 1 cultivator for 2 fields of waqf land for ponds. The implementation of the inventory function has not been carried out properly, namely, there are still 4 fields of waqf land that have not been certified, the implementation of the productivity inventory function is not good, by leaving waqf land idle not planted during the rice planting season.